HASAN BASHRI DAN TRADISI SUFISME - irfaan, santosa (Jurnal Bestari, 1994)
Hasan Bashri is a pioneer or, a little further, a figure of change between common and sufic ascetic. Besides, he was still in the pattern of common 'zuhud', that is only motivated by al-khauf wa al-raja', the fear (anxiety) of Allah's anger through His tortures and overcome by the hope of God's favor and heavenly reward.